Socialization About The Benefits Of Using BPJS Kesehatan In 15th Hamlet Sukamentri Urban Village Garut Kota District, Garut Regency (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
BPJS Kesehatan is the legal entity administering social security in the health sector. The health program is undertook the National Health Insurance. The entity was a replacement for Askes for civil servants and Jamsostek for non-civil servants. All Indonesian citizens are required to set aside their income for future health insurance. Thus all governments in all regions in Indonesia formed BPJS Kesehatan. It is recorded that up to 2021, 83.89% have been registered as participants of BPJS Kesehatan. So this program is also running in West Java, including Garut Regency where the participants in 2022 have reached 85%. However, there are problems in its implementation, that is awareness in paying dues as evidenced by the large number of participants who are in arrears. The PPM team decided to do community service in one of the downtown areas of Garut Regency, namely in 15th Hamlet, Sukamentri Urban Village, Garut Kota District. The results of the initial review, the participants of BPJS Kesehatan here are classified as low. The PPM team assumed that cause was the low level of community knowledge. So the purpose of this service is increasing the knowledge level of the people in 15th hamlet, Sukamentri Urban Village, Garut Kota District about BPJS Kesehatan. The method is counseling to the community and its leaders. The result is an average pretest of 42.58 and average posttest of 63.81. The conclusion that there was increase the knowledge level of the  15th Hamlet Sukamentri Urban Village community about BPJS Kesehatan. Keyword: BPJS Kesehatan, Health Insurance, Knowledge level